Emergency Nursing Intervention and the Outcome towards Trauma Patients in the Emergency Department: A Scoping Review - Siti Nurlaelah; Arcellia Farosyah Putri; Fatriani; Rahmi Istanti (Fakultas Keperawatan Universitas Andalas, 2025)
The precision of management protocols largely influences the outcomes of trauma patients. Nurses play a crucial role in patients’ stabilization. Accurate and timely screening can improve the response time and facilitate the effective stabilization of trauma patients. This review aims to understand: (1) Types of emergency nursing intervention delivered for trauma patients in the emergency department, (2) Outcomes from the emergency nursing intervention delivered for trauma patients in the emergency department. A scoping review was conducted following Arksey and O’Malley’s approach and Levac’s method for data analysis. Interventions conducted by nurses in the emergency department for trauma patients included Airway – Breathing – Circulation – Disability – Environment/Emotional care – Foley catheter – Gastric tube – Hemodynamic monitoring – Interprofessional teamwork. Outcomes related to emergency nursing intervention can be divided into three categories: patient, nurse, and organizational outcomes. Emergency nursing interventions are most effective in better managing trauma patients when grounded in competency-based education, delivered through standardized protocols, supported by interdisciplinary teamwork, and inclusive of emotional and psychological care.